Methods to homogenize and fill the wind data from the meteorological tower of Villonaco Wind Farm in Loja-Ecuador - Diego Jijón; Jessica Constante; Marcelo Moya; Gonzalo Guerrón (ACI Avances en Ciencias e Ingenierías, 2015)
A new methodology of wind data processing used in feasibility and optimization of wind farms is presented in this work. The wind data of the meteorological tower provided by CELEC-EP is analyzed through a quality control of suspicious values, according to wind speeds greater than 50 (m/s) and a daily statistical relationship proposed in this work for the wind measurements at 20, 40 and 60 meters high. The suspicious values are processed and filled across of the statistical relationship among the different wind speed data at the three heights of measurement as a multivariate function. On the other hand, the turbulence intensity behaves as an exponential decay function of the average and standard deviation wind speed data. This work analyzes two methodologies for missing wind speed data filled, both were compared and one is chosen for wind data processing. The wind speed data quality control and homogenization were automatized since the supervisory control and data acquisition system “SCADA” of the Villonaco Wind Farm.